Depression and Anxiety in Patients with Alcoholism Complicated by Nicotine Addiction (Eurasian Medical Research Periodical, 2022)
research confirms the observation that “smokers drink and drinkers smoke”. In this study, we assess the relationship between nicotine dependence and the degree of anxiety and depression among alcohol dependent patients. The study involved 75 inpatients with a diagnosis of alcohol dependence. They passed the Fagerstrom test for nicotine addiction, the Hamilton Anxiety and Depression Scale.